Bentham's Theory of Evidence: Setting a Context1. (12th July 2019) - Twining, William
Abstract : page_20 other Bentham's massive writings on evidence, procedure and judicial organisation (EPJ) survive in over 13, 000 pages of manuscript in addition to 15–20 published works, for some of which full manuscripts no longer survive. These are all quite closely linked. In order to start to understand the Rationale of Judicial Evidence it is useful to consider it in three broad contexts: Bentham's other works in addition to those on EPJ, especially those works on the pannomion and the constitutional writings; attempts to construct a 'theory of (judicial) evidence' in the Anglo-American tradition of common law, especially those of J. B. Thayer and J. H. Wigmore; and recent efforts at UCL and elsewhere to develop evidence as a distinct multi-disciplinary field.